Comparative characteristic of laboratory indicators for encephalitis, disseminated encephalomyelitis and multiple sclerosis in children - E. Y. Skripchenko; L. A. Alekseeva; N. V. Skripchenko; T. V. Bessonova (Русский журнал детской неврологии)
Background. The similarity of the clinical manifestations of encephalitis (E), disseminated encephalomyelitis (DEM) and multiple sclerosis (MS) in children, the complexity of predicting the nature of the course and outcome of diseases determines the search for additional diagnostic and prognosis criteria.Objective: a comparative characteristic of laboratory indicators for E, DEM and RS in children to assess their diagnostic and prognostic value.Materials and methods. Fifty six children (14 children with E, 14 – with DEM, 28 – with MS) and 16 children of the control group (with acute respiratory virus infection) at the age from 10 to 17 years were examined. Laboratory methods included standard studies of cerebrospinal fluid (protein, cytosis), determination of concentrations of albumin and immunoglobulin G (IgG) in cerebrospinal fluid and serum with subsequent calculation of protein indices (albumin, immunoglobulin, intrathecal immunoglobulin G indexes).Results. With all nosological forms in the serum there were no significant differences between albumin and IgG from the control group, whereas in the cerebrospinal fluid an excess of the concentration of IgG was detected at a normal level of albumin. An increase in the albumin index was found only in E, whereas the immunoglobulin index was significantly higher than the norm in all groups of patients. A significant spread of the intrathecal IgG index (from 0.1 to 11.9) was found, which determined the analysis of clinical and laboratory parameters by subgroups, depending on its magnitude. The maximum incidence of increased intrathecal IgG synthesis was detected in children with MS (with exacerbation of MS – 74 %, in remission – 67 %), whereas in E and DEM, an increase was observed in about half of the patients surveyed and associated with a more favorable course of the disease.Conclusion. The data obtained make it possible to assert that, despite the commonness of some pathogenetic mechanisms, there are differences in the degree of impaired permeability of the blood brain barrier, the intensity of the systemic and intrathecal humoral immune response in E, DEM and RS, which may determine the features of their course and the outcome of the disease, including the transformation of the DEM in the RS.